Comparative of Financial Performance Ratio of Mining Companies Listed on The Indonesia Stock Exchange in Three Period - Maylizza Putri Dyansyah; Dhea Rizky Istiqomah; Nur Aini; Fara Brygita Ramadhani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study was conducted with the aim of assessing the financial performance of mining industry companies, namely PT Indo Tambangraya Megah Tbk (ITMG), PT Mitrabara Adiperdana Tbk (MBAP), PT Bukit Asam Tbk (PTBA), and PT Aneka Tambang Tbk (ANTM). ) during the 2019-2021 period to the industry average ratio or using the Cross-Section method analysis. The type of research used is descriptive-quantitative research, where after calculating and comparing the ratio of the company to the industry, a descriptive analysis is then carried out. The data source used is the results of previous research on financial ratios in the four companies for the 2019 – 2021 period. The results of the research obtained during the period 2019 - 2021 the company PT Mitrabara Adiperdana Tbk (MBAP) had very good performance, this is evidenced by the majority of the value of the company’s financial ratio is above the value of the industry average ratio every year, for example, the liquidity ratio of PT Mitrabara Adiperdana Tbk has a ratio value during 2019 - 2021, namely 360.4%, 374.4%, and 397.8%, respectively, where the average industry value for three periods is only between 220% - 275%. The management of MBAP company assets/assets is also considered good as evidenced by the asset turnover ratio, which has the highest average value of 4.8 rounds. In solvency ratio and profitability ratio, MBAP is the highest among the four companies, and above the industry average ratio. However, the MBAP market ratio has the lowest ratio results during 2019 - 2021 among companies and the industry average. s financial ratio is above the value of the industry average ratio every year, for example, the liquidity ratio of PT Mitrabara Adiperdana Tbk has a ratio value during 2019 - 2021, namely 360.4%, 374.4%, and 397.8%, respectively, where the the average industry value for three periods is only between 220% - 275%. The management of MBAP company assets/assets is also considered good as evidenced by the asset turnover ratio, which has the highest average value of 4.8 rounds. In solvency ratio and profitability ratio, MBAP is the highest among the four companies, and above the industry average ratio. However, the MBAP market ratio has the lowest ratio results during 2019 - 2021 among companies and the industry average.